THE PHYSICAL EDUCATION AND THE TAKING OF CONSCIENCE OF THE MOTOR ACTIONS (Fiep Bulletin - online, 2014)
Main the characteristics of discipline of Physical Education were to be activity area and it was always worried about the education of the movement, seeing it as a manifestation mechanics only. In the last decades that this disciplines it only started to be understood as knowledge area. Its objective is to contribute for the construction and agreement of the motricity human being. For that is indispensable the conscience taking that initially structure in acts, and later become in the thought condition. We have in a first level the exercitação of the consequences. The acquired adaptations or habits that add to this functioning the newness of the external way, through primary the circular reactions are followed. The secondary circular reactions mark the third level and guarantee the repetition of the permanent spectacles, even so the differentiation enter projects half e ends happen a posteriori, occurring the taking of conscience in acts. The conscience characterizes in the room level when it has a distinction between project half e ends, therefore the subject one passes of the analysis of the results of its action for the ways that make possible the success. It has then internal mobility to the project and in the coordination between the scheme, that can be separable to be regrouped of different form. It has, in the ticket for the fifth phase, an enrichment of the projects that the citizen will allow to try, to try to solve the challenges, new half projects. This confers in the sixth level a bigger refinement of the coordinations; the citizen already is capable to evoke new ways for mental combination. The conscience taking is guaranteed through a process that has left of practical intelligence and walks in the direction of reflected intelligence. Being thus the Physical Education it must provide to the pupils the construction and the agreement of its motricity; it is indispensable to argue the relation between making and understanding that structure gradual the measure that the citizen takes conscience of its action.
Keywords: Physical Education; Taking of Conscience; Motor Action